2017
DOI: 10.1002/cam4.1039
|View full text |Cite
|
Sign up to set email alerts
|

CCR7 mediates human breast cancer cell invasion, migration by inducing epithelial–mesenchymal transition and suppressing apoptosis through AKT pathway

Abstract: Chemokine and the chemokine receptor have a key role in the tumor progress. Here, we supposed that CCR7 might induce the invasion, migration, and epithelial–mesenchymal transition (EMT) process of breast cancer. In this research, human breast cancer MCF‐7 and MDA‐MB‐231cells were treated with CCL19 and small‐interfering RNA (CCR7 siRNA) for activation and inhibition of CCR7, respectively. Cell invasion and transwell assays were used to detect the effect of CCR7 on invasion and migration. The results demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…CCL21 induces actin polymerization and migration. [18,[44][45][46] Human Bladder Cancer Enhances the migration, invasion and tumor proliferation/ correlates with poor prognosis. [43,47] Cervical Cancer Metastasis and poor prognosis.…”
Section: Tumor Type Observations Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…CCL21 induces actin polymerization and migration. [18,[44][45][46] Human Bladder Cancer Enhances the migration, invasion and tumor proliferation/ correlates with poor prognosis. [43,47] Cervical Cancer Metastasis and poor prognosis.…”
Section: Tumor Type Observations Referencesmentioning
confidence: 99%
“…It has been illustrated that CCR7 triggers AKT which eventually leads to the secretion of MMP-2/9. The silencing of CCR7 thus acts as a targeted therapy to inhibit AKT and MMPs expression and attenuates MCF-7 cell proliferation, invasion and EMT [45]. A schematic illustration of CCR7 binding to the cognate ligands CCL19/CCL21 to induce several signaling transduction pathways in breast cancer is shown in (Figure 2).…”
Section: Molecular Aspects Of C-c Chemokine Receptor 7 (Ccr7) Signalimentioning
confidence: 99%
See 1 more Smart Citation
“…5860 Similar observations have been reported for the CCR2-CCL2, CCR5-CCL2,3,4,5, CCR7-CCL19,21 and CCR8-CCL18 axes. 6169 The role of FPR1 in tumor progression remains controversial as it has been associated with tumor invasion in colorectal cancer but with tumor suppression in gastric cancer. 70,71 As far as P2RY6 is concerned, Placet et al recently suggested its role in cancer cell survival.…”
Section: Resultsmentioning
confidence: 99%
“…In particular we focus on tumor size and metastatic risk status of the tumor. Patient data suggests that AI therapy increases the expression of both PD-L1 and chemokine receptor CCR7 in tumors (3), both of which are associated with increased (4)(5)(6). Analysis of the therapeutic interactions suggests that there may be tradeoffs between tumor size and metastatic potential, and to this end we have developed a suite of mathematical models to investigate this interaction with the goal of eventually developing a dynamic PEPI score.…”
Section: Introductionmentioning
confidence: 99%